On the Causal Nature between Financial Development and Economic Growth in the Democratic Republic of the Congo: Is it Supply Leading or Demand Following? - PINSHI, Christian P. (Journal of Advanced Studies in Finance; Vol 11 No 2 (2020): JASF Volume XI Issue 2(22) Winter 2020, 2020)
This paper seeks to study and answer the question on the nature and direction of the causality between financial development and economic growth in the Democratic Republic of the Congo (DRC) using data from 2004 to 2019. The long-term relationship not being robust, we opted for the short-term dynamics with the causality test in the sense of Granger to support this question. The results indicated the existence of a one-way causality from economic growth to financial development. This result is in line with the Demand following hypothesis, given the country’s economic and financial landscape, which presents a less deep financial system. Consequently, choices of growth policies (increase in knowledge, infrastructure, pleasant business climate, structural reforms, etc .) should be adopted to enhance and develop the Congolese financial system. However, we recognize that once growth is restored and becomes sustainable, financial development could lead to sustained and resilient economic growth.